The effect of intensive resistance exercise and excessive fructose intake on metabolic and physiological responses - Chien-Hua Chen; Shun-Hsi Tsai; Hao-Chien Cheng; Yu-Ting Su; Hung-Wen Liu (Nutrition & Metabolism)
Abstract Background Muscle-derived uric acid (UA) precursors combined with fructose ingestion may increase liver UA production. Temporary hyperuricemia could impact metabolic and physiological responses over a 24-h period. This study examined the effects of intensive resistance exercise (RE) combined with excessive fructose intake on metabolic and physiological responses. Methods Twelve healthy young males participated in four trials: RE with fructose intake (EF), RE with water intake (EW), control (no exercise) with fructose intake (CF), and control with water intake (CW). Blood UA, glucose, lipids, blood pressure, and markers of kidney and liver function were measured during fasting and at 0, 0.5, 1, 2, 4, and 24 h before and after exercise. Results UA levels in the EF and EW trials were significantly higher than those in the CF and CW trials at all post-exercise time points. The next morning, UA levels in the EF trial remained above 7 mg/dL. Increased glucose levels at 0 and 0.5 h post-exercise and increased creatinine (CRE) levels immediately post-exercise were observed. RE reduced the area under the curve for the estimated glomerular filtration rate (eGFR) and increased systolic blood pressure, mean arterial blood pressure, and the UA/CRE ratio the next morning. Fructose intake increased glutamate pyruvate transaminase (GPT) levels 24 h post-exercise. CRE showed a positive correlation with UA levels, while eGFR was negatively correlated with UA levels in the RE trials. Additionally, GPT levels correlated positively with UA following fructose intake. Conclusion Intensive RE combined with excessive fructose intake induced a notable increase in UA levels. This increase in UA levels appeared to be associated with temporary fluctuations in markers related to renal function.